Study on Aspects of the PEA of Business Administration Students of the UAJMS of Tarija in the Context of the Covid 19 (Global Journal of Management and Business Research, 2020)
Currently, the aspects of the teaching and learning process in higher education are relevant and play an important role in the academic offer. The objective of this study seeks to systematically identify the fundamental aspects of educational teaching work based on the Teaching-Learning Process., in a different context than usual, in order to be able to provide feedback on the PEA.
Keywords: PEA teaching-teaching teaching process: value judgments and monitoring